Isolation of Burkholderia cepacia Complex from Pericardial Fluid in a Patient with Lung Adenocarcinoma with Metastasis: A Rare Case Report - K, Mirlekar; M, Saraf; A, Sarage (International Journal of Clinical Microbiology, 2026)
Burkholderia cepacia complex was isolated from pericardial fluid in a patient with metastatic lung adenocarcinoma, representing a rare opportunistic pericardial infection. Clinical improvement following targeted antimicrobial therapy supported its pathogenic significance and highlights the importance of microbiological evaluation of malignant pericardial effusions.
Keywords: Burkholderia cepacia complex; pericardial fluid infection; lung adenocarcinoma metastasis; opportunistic infection; malignant pericardial effusion